The enthymeme : syllogism, reasoning, and narrative in ancient Greek rhetoric - Fredal, James, 1961- (The Pennsylvania State University Press, 2020)
"Examines the concept of the enthymeme in ancient Greek rhetoric, arguing that it is a technique of storytelling aimed at eliciting from the audience an inference about a narrative"--